Sleep disturbance in children with attention-deficit hyperactivity disorder: A systematic review - Martins R.* (2019)
© 2019 Brazilian Association of Sleep and Latin American Federation of Sleep Societies. All rights reserved.The aim of the present systematic review was to compare sleep disorders in children, from 7 to 12 years old, with and without an attention-deficithyperactivity disorder (ADHD) diagnosis. Electronic literature search of PubMed, LILACS, Scopus, Web of Science and Cochrane Library databases was conducted in September 2017. We included cross-sectional observational studies comparing the sleep of children between 7 and 12 years old, with and without an ADHD diagnosis, reported according to the Diagnostic and Statistical Manual of Mental Disorders criteria. The studies with other research designs, those that included adolescents and/or adults in the sample and those who evaluated the sleep of children with ADHD and other associated comorbidities were excluded. A total of 1911 articles were identified. After analyzing, 8 articles were compatible with the theme and included in the review. For sleep evaluation, most of the studies used an objective measure together with another subjective measure. Three out of six studies that used objective measures did not observe any differences between children with and without ADHD diagnosis. Children with ADHD presented more sleep disturbances when compared to children without the diagnosis. These disorders were diverse, yet inconsistent among the surveys. More studies are needed to clarify and for robust results.